Atraumatic Restorative Treatment: A narrative review on its concepts and applicability (Research, Society and Development, 2024)
The article addresses the importance of oral health for the overall development of the individual and the significance of dental caries, especially in children in Brazil. The objective of this study is to present a literature review on Atraumatic Restorative Treatment (ART). The article presents data on the prevalence of caries, such as the "Global Burden of Disease Study 2019," which shows a high incidence of dental caries, and the 2020 SB Brasil statistics. Atraumatic Restorative Treatment (ART) is a minimally invasive approach that aims to preserve healthy tooth structure and is particularly useful in areas with limited resources. Developed by Jo Frencken in the 1980s, ART uses manual excavators and glass ionomer cement (GIC) to treat caries without the need for complex dental equipment, such as drills and anesthesia. Through a narrative review, the article discusses the effectiveness of ART, its advantages, such as low cost and less trauma for the patient, and its limitations, including the lower mechanical strength of GIC compared to other restorative materials. ART is promoted by health policies in Brazil and has proven effective in vulnerable communities. The technique is indicated for various types of dental restorations, although it has some contraindications. The review concludes that ART is a valuable solution for the treatment of caries, especially in resource-limited settings, and emphasizes the need for more research and public policies to improve oral health in underserved populations.